Practice of Electrical Insulation of Lightning Protection Systems in India – Before and After the Publication of the National Building Code of India 2016 - Gopan, Nandu; Gopan, Anandu (Amrit Research Journal, 2024)
Lightning protection system (LPS) as per IS/IEC 62305 is mandatory in India for buildings above 15 meters and for special buildings like educational institutions, and hospitals regardless of their height. External LPS (ELPS) can be of isolated or non-isolated type depending upon the nature of the structure. This paper reviews the installation of ELPS before and after the publication of the National Building Code of India 2016 (NBC). This is limited only to ELPS and Internal Lightning protection system (ILPS) is not considered. The installation has been studied as per IS/IEC 62305 on electrical isolation. The conclusion has been drawn based on the installation and the influence of NBC 2016.